Teacher Creativity in The 21st Century : An Analysis of The Influence of Principals' Leadership, School Culture, and Work Motivation - Octavia, Maria; Suharyati, Henny; Patras, Yuyun Elisabeth (Jurnal Paedagogy, 2025)
This study aims to investigate the relationship between principal leadership, school culture, work motivation, and teacher creativity in private elementary schools located in the Central Bogor District, West Java. This study uses a quantitative approach with a survey method and data analysis using a Structural Equation Modeling approach with the Partial Least Squares (SEM PLS) method. The research sample consisted of 118 respondents, who were assessed using a rating scale for the variables of Teacher Creativity and Principal's Leadership, and a Likert scale for the variables of School Culture and Work Motivation. The results of this study show that the leadership of school principals has a significant role in encouraging teacher creativity in elementary schools. Additionally, the principal's leadership and school culture have been shown to enhance teachers' work motivation. However, work motivation does not directly contribute to increasing teacher creativity. It does not function as a mediator in the relationship between the principal's leadership or school culture and teacher creativity. The implications of this study suggest that there is a need for a leader who can apply a transformational and participatory leadership style, enabling teachers to feel more motivated to develop their skills. In addition, teachers need to actively manage their intrinsic motivation so that they exhibit curiosity, critical thinking, flexibility, a desire to create new ideas, and a practical problem-solving approach.